Assessment Test of Receptive Skills: Listening and Reading Comprehension of Recount Text Using AI Platfrom (Atomic Learning) - Fakhrurriana, Ria; Herdina, Griseldis Faden (Proceeding International Conference on Religion, Science and Education, 2024)
Receptive skill is the ability to understand language especially listening and reading. From listening and reading, someone can understand the meaning of something that given to them in order to do something or activity as the respond. There are many materials in English one of them is recount text. However, some articles explain about receptive skills in general such as assessment in reading and listening for students or it can be one of method that researcher uses in assessment of listening and reading use AI platform (Atomic Learning). Therefore, this article discusses about assessment test of receptive skills in listening and reading comprehension especially in recount text using Atomic Learning. Moreover, this article limits on assessment for listening and reading of recount text especially for class 10 students of senior high school. In the assessment of receptive skills, there are many differences of assessment between listening and reading comprehension of recount text depending on students’ assessment necessity for their understanding about the material. Thus, this article is very important to read by the readers who want to know the assessment test of receptive skills listening and reading comprehension of recount text using AI platform especially Atomic Learning.